ESTIMATION OF VARIANCE COMPONENTS AND SOME GENETICS PARAMETERS FOR MILK YIELD IN WATER BUFFALO POPULATION RAISED IN ISTANBUL - K. Yazgan; M. İ. Soysal; Y. Öner; E. K. Gürcan; E. Ö. Ünal (Journal of Animal and Plant Sciences, 2024)
This study aims to estimate variance components, heritability, and repeatability of lactation yield (270 day), as well as estimated breeding value for 879 water buffalo lactation records for 615 animals belonging to the water buffalo breeding project using BUGA software. The model was constructed by using all available the pedigree information. Herd, season and year were used as fixed effects while lactation length and age were used as covariate. Random environment variance, genotypic variance and permanent environment variance values were estimated as 48388.61±0.0003 kg2, 12003.08±0.0003 kg2 and 9567.92±0.0003 kg2 while heritability (h2) and repeatability (r) of lactation yield were estimated as 0.17 ±0.162 and 0.30, respectively. The study concluded that the heritability of milk yield was low and in order to achieve more effective genetic improvement, the project should be organized in a way that allows for the identification of sire records for the animals involved.In addition, the environmental conditions in which buffalos are raised must be brought closer to the conditions required by the animals.
Keywords: water buffalo; estimated breeding value; BUGA software; genetic parameter